Development of Inventory Management Application Points Of Sale Using Laravel - Hanafi Kambivi; Eko Junirianto; Nisa Rizqiyah Fadhliyah (TEPIAN, 2020)
development of the business world encourages companies to always try to improve the quality of products and services to consumers. The implementation of these business solutions is a commitment in increasing the competitive advantage of corporate customers in terms of efficiency, effectiveness, performance, and business development. The purpose of this research is to conduct an analysis and design of a point of sale (POS) management application to support the purchasing service system and stock of goods that can help small and medium entrepreneurs in data management. The making of this POS application starts from collecting all the data needed using observation and interview methods, designing an application model with an object-based diagram approach with application design tools in the form of flowchart and Unified Modeling Language (UML) until the implementation of this POS application. With the application of the point of sales (POS) application can help the tasks of related parties or all stakeholders directly related to the POS application.